IMPLEMENTASI LOAD BALANCING DAN FAILOVER PADA JARINGAN INTERNET MENGGUNAKAN METODE NTH - Idham; Rodianto; Hendra Wahyudi (Jurnal Informatika Teknologi dan Sains, 2022)
Abstract: This study discusses the implementation of load balance and failover using the NTH method. The implementation of the load balancing method is carried out using the MikroTik RouterBoard. The tests carried out are to measure the performance of network connectivity, failover mechanisms and network Quality of Service (QoS) from the load balancing method of this study using the NDLC method as a method of network development. The results of implementing this load balance show throughput of 79%, packet loss of 0.69%, delay of 55.3ms and jiter of 0.851ms which based on the TIPHON standard are included in the very good category. And the results of testing using a speed test show that the download and upload results are consistent with the download results of 24.72 Mbps and upload of 18.27 Mbps